Work-Related Risk Factors of Knee Meniscal Tears in Korean Farmers: A Cross-Sectional Study - Chae Young Hong; Chul Gab Lee; Dong Hwi Kim; Yong Soo Cho; Kweon Young Kim; So Yeon Ryu; Han Soo Song (Elsevier, 2020)
Background: Meniscal tears are among the major risk factors for knee osteoarthritis progression. This study aimed to investigate the relationship between meniscal tears and work-related factors in the farming occupation. Methods: The participants included 486 farmers (238 men and 248 women), aged 40-69 years, who were among the 550 farmers registered in the Korea Farmer's Knee Cohort (KFKC). Data such as those on gender, age, body mass index (BMI), mechanical axis, cumulative heavy-lifting working time (CLWT), cumulative squatting working time (CSWT), and previous knee injury history were collected from the questionnaire, along with whole leg radiographic findings. Two radiologists assessed the magnetic resonance images of both knees to confirm the presence of meniscal tears. The factors related to meniscal tears were analyzed by multiple logistic regression. Results: A total of 54.5% of the farmers (48.7% of men and 60.1% of women) had meniscal tears. These tears were associated with gender, age, and BMI. We also identified an association between meniscal tears and CSWT, an especially important factor in farming [10,000-19,999 working hours, odds ratio = 2.16, 95% confidence interval (CI): 1.14-4.07, ≥20,000 working hours, odds ratio = 2.35, 1.45-3.80]. However, mechanical axis, knee injury history, and CLWT were not significantly related to meniscal tears. Conclusion: This study's findings show that squatting for long periods, as an occupational factor, is related to meniscal tears.